2023
DOI: 10.1002/jcop.23048
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of the structuring of questions about sexual orientation and gender identity

Abstract: The purpose of this scoping review is to map the extent of the current research on how to best structure questions asking respondents to self‐identify their sexual orientation and gender identity and to ascertain what further issues about measurement need to be explored. Using the Arksey and O'Malley framework for scoping reviews, 52 articles describing primary research about how to structure sexual orientation and gender identity (SOGI) questions, published in the years 2000–2021, were identified and analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 58 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…The second reason most cited was the aversion to using a condom, more frequently cited among people with a low educational level. A recent systematic review revealed homosexual men believe that not using condoms represents mutual trust and loyalty between sexual partners, while condom use is a symbol of distrust or suspicion regarding the partner’s HIV status [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The second reason most cited was the aversion to using a condom, more frequently cited among people with a low educational level. A recent systematic review revealed homosexual men believe that not using condoms represents mutual trust and loyalty between sexual partners, while condom use is a symbol of distrust or suspicion regarding the partner’s HIV status [ 32 ].…”
Section: Discussionmentioning
confidence: 99%